Marketing Communications Strategy in Increasing the Number of Visits to Rice Tourism Destinations - Ike Purwaningrum; Mujahid Mujahid; Fitriana Fitriana (Journal La Bisecoman, 2024)
This research aims to analyze the marketing communication strategy of the Rice Field Tourism Destination in Gunung Mulia Village, as well as the inhibiting and supporting factors of these strategies in increasing the number of tourist visits. The research method employed is qualitative descriptive, with data collection through in-depth interviews, observations, and document studies. Data analysis utilizes content analysis. The research findings indicate that out of the 5 promotions mix in the marketing communication strategy, only three are implemented by D’Wish, namely advertising strategy, sales promotion, and direct marketing. Meanwhile, personal selling, public relations, and publicity have not been applied. The primary inhibiting factor affecting the implementation of the entire strategy is budget limitations, leading to selectivity in choosing marketing communication strategies. On the other hand, there are supporting factors contributing to the success of D’Wish's marketing communication strategy. These include affordable entrance tickets, the absence of competitors in the surrounding environment, and the availability of social media as an effective platform for advertising and promoting D’Wish. This research provides recommendations for destination managers to consider developing a more holistic and optimal marketing communication strategy to overcome budget constraints and leverage the advantages of existing supporting factors.